Design and Experimentation of CP Sequential-Rotated Patch Antenna for Nanosatellite Technology - Nathapat Supreeyatitikul; Kittisak Phaebua; Chuwong Phongcharoenpanich; Jessada Konpang (My University, 2024)
This paper proposes a circularly polarized (CP) sequential-rotated patch antenna for nanosatellite communication systems. The proposed CP sequential-rotated patch antenna comprised of 2 × 2 corner-truncated rectangular patch with a slot, and sequentially rotated feeding (SRF). The SRF was used to improve impedance matching and CP bandwidth. These patches and SRF were fabricated on Rogers 5880 substrate. Moreover, this antenna was integrated with radome and enclosures for space environment hazards. The measured results at 2.1 GHz (center frequency) achieved RLBW of 73.33% (1.46 - 3 GHz) and ARBW of 23.33% (1.87 - 2.36 GHz). The optimal gain (RHCP) was 5 dBic at 2.25 GHz with bi-directional radiation, rendering the proposed antenna suitable for S-band nanosatellite technology.
Keywords: Spacecraft Design and Technology; Satellite Communication Systems; Antenna Design and Optimization